Proceeding of Fourth International Conference on Spoken Language Processing. ICSLP '96
DOI: 10.1109/icslp.1996.607059
|View full text |Cite
|
Sign up to set email alerts
|

Subglottal pressure and final lowering in English

Abstract: Quantitative models of intonation in a variety of languages typically specify a long-range downtrend across the sentence that provides a declining backdrop for the steeper rises and falls of more local pitch events such as accents and word tones. Several studies of this "declination" in English and several other languages have isolated a component of somewhat steeper decline that covers only the last few centiseconds of "lab speech" utterances. Other studies suggest that this "final lowering" may be particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…We call this phenomenon positional reduction. A few recent reports have found similar effects variously attributed to supralaryngeal declination [Vaissière, 1986;Vayra and Fowler, 1992;Krakow et al, 1995], initial strengthening [Jun, 1993;Fougeron and Keating, 1997], or final fade [Herman et al, 1997]. Our study is similar to the study of Swedish vowels reported by Nord [1986] in that we find that final vowels though longer than initial vowels are nonetheless reduced.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…We call this phenomenon positional reduction. A few recent reports have found similar effects variously attributed to supralaryngeal declination [Vaissière, 1986;Vayra and Fowler, 1992;Krakow et al, 1995], initial strengthening [Jun, 1993;Fougeron and Keating, 1997], or final fade [Herman et al, 1997]. Our study is similar to the study of Swedish vowels reported by Nord [1986] in that we find that final vowels though longer than initial vowels are nonetheless reduced.…”
Section: Introductionsupporting
confidence: 80%
“…The unifying factor seems to be that syllables toward the ends of prosodic constituents are produced with less articulatory effort than the other syllables in an utterance. This focus on the ends of prosodic units underlies the term 'final fade' [Herman et al, 1997] to describe a complex of acoustic and articulatory phenomena which occur at the ends of prosodic units, as well as the 'sonority' theory of articulatory dynamics [Beckman et al, 1992] in which final prosodic edges are characterized by reduced gestural stiffness -giving rise to final lengthening and perhaps also positional reduction. However, other researchers looking at apparently similar phonetic phenomena have adopted a somewhat different focus.…”
Section: Positional Reductionmentioning
confidence: 99%
“…For instance, the cricothyroid and thyroarytenoid muscles act synergistically to achieve changes in fundamental frequency (Ohala, 1978;Titze, Luschei, & Hirano, 1989) and the role of the cricothyroid depends upon vocal fold position at the time of contraction (Kuna, Smickley, Vanoye, & McMillan, 1994;Titze et al, 1989). Fundamental frequency rises and falls can also be achieved by increases or decreases of subglottal air pressure (Herman, Beckman, & Honda, 1996;Monsen, Engebretson, & Vemula, 1978). Subglottal pressure changes are mainly achieved by muscles that adjust the pulmonary system.…”
Section: Laryngeal Mechanisms Responsible For Fundamental Frequency Rmentioning
confidence: 99%
“…However, the significant positive and negative connection of the insula and LMC seems to be contrary to the above mentioned single passive mechanism hypothesis. Furthermore, the rise and fall of fundamental frequency may also have involved increased or decreased subglottal air pressure (Herman et al, 1996;Monsen et al, 1978), Brain regions involved in respiratory control, especially the inferolateral sensory region and auditory cortex associated with expiration, may also be involved in fundamental frequency control (Ludlow, 2005). Thus, it is possible that multiple neural mechanisms are involved.…”
Section: The Contrast Between the Neural Mechanisms For Tone Rise Andmentioning
confidence: 99%
“…They thought that a drop in the subglottal pressure and relaxation of the laryngeal muscles were necessary articulatory correlates to final lowering. This claim was followed by Herman, Beckman and Honda [14], who considered final Ya Li, Hao Che, Shanfeng Liu, Jianhua Tao National Laboratory of Pattern Recognition, Institute of Automation, Chinese Academy of Science, Beijing, China {yli, hche, sfiiu, jhtao}@nlpr.ia.ac.cn lowering as one of the products of an overall "vocal effort" decrease towards the end of an utterance. This decrease would result in a drop in both subglottal pressure and gesture stiffness, and cause a series of chain reaction including segmental lengthening, average amplitude decreasing, voice quality changing and final pitch lowering.…”
Section: Introductionmentioning
confidence: 94%